Holy ground: where art and text meet : studies in the cultural history of India - Bakker, Hans T. (Gonda indological studies, 2019)
The 31 selected and revised articles in the volume Holy Ground: Where Art and Text Meet, written by Hans Bakker between 1986 and 2016, vary from theoretical subjects to historical essays on the classical culture of India. They combine two mainstreams: the Sanskrit textual tradition, including epigraphy, and the material culture as expressed in works of religious art and iconography. The study of text and art in close combination in the actual field where they meet provides a great potential for understanding. The history of holy places is therefore one of the leitmotivs that binds these studies together. One article, "The Ramtek Inscriptions II", was co-authored by Harunaga Isaacson, two articles, on "Moksadharma 187 and 239-241" and "The Quest for the Pasupata Weapon," by Peter C. Bisschop.